A Systematic Review of Total Dislocation of the Talus - Weston, John T. (Orthop Surg, 2015)
This review summarizes the treatment and resulting outcomes for total talar dislocation. The PubMed database was searched for articles about humans with total talar dislocation published in the English language in the last twenty years. The following data were entered into a Microsoft Excel spreadsheet: type of dislocation, nature of associated fractures (if any), type of reduction/fixation utilized, immobilization, weight‐bearing status, outcome, complications and average follow‐up time. Thirty‐nine articles reporting a total of 86 cases of total talar dislocation are included in this review. Seventy‐three of these were open injuries and 13 closed. Forty‐three cases had an associated foot or ankle fracture, 32 of those cases specifically having a fracture of the talus. The talus was preserved in the initial management of 74 cases, whereas the remaining 12 cases were managed by primary talectomy. The mean duration of follow‐up was 32 months. Twenty‐two cases required a secondary arthrodesis or another additional procedure. A good outcome was achieved in 35% of cases, a fair outcome in 37% and a poor outcome in 27%. The complication of avascular necrosis (AVN) occurred in 22 cases and 14 subjects developed clinically significant osteoarthritis. Generally, the outcome of current treatments associated with total talar dislocation is not ideal, only 1/3 of cases achieving good outcomes. So far, preservation of the talus is the best treatment option. AVN is still a relatively common complication even in the absence of fracture or postoperative infection.